2013
DOI: 10.1080/07347324.2013.771977
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Feedback-Based Brief Intervention to Reduce Alcohol Use in Community Substance Use Disorders Treatment

Abstract: Feedback brief interventions for alcohol use problems have been highly effective with undergraduate populations. However, there has been little research on the effectiveness of administering feedback alone to community treatment populations. The goal of the current study was to assess the effectiveness of a feedback brief intervention in a community treatment setting with patients characterized largely by dependence on alcohol and drugs, ethnic diversity, and low socioeconomic status. It was hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Community-based non-profit treatment centers treat clientele who are less educated and have more risk factors that are associated with poorer alcohol use treatment outcomes (Worden & McCrady, 2013). EAs obtaining little postsecondary education have higher substance use (Oesterle, Hawkins, & Hill, 2011; Thompson, Stockwell, Leadbeater, & Homel, 2014) and college attendance is associated with both treatment retention and completion (Sahker, Acion, & Arndt, 2014).…”
Section: Introduction 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based non-profit treatment centers treat clientele who are less educated and have more risk factors that are associated with poorer alcohol use treatment outcomes (Worden & McCrady, 2013). EAs obtaining little postsecondary education have higher substance use (Oesterle, Hawkins, & Hill, 2011; Thompson, Stockwell, Leadbeater, & Homel, 2014) and college attendance is associated with both treatment retention and completion (Sahker, Acion, & Arndt, 2014).…”
Section: Introduction 10mentioning
confidence: 99%
“…First, studies were located on college campuses, so it is unclear if findings would replicate with EAs treated in off campus community agencies. As noted above, publicly funded treatment agencies typically serve individuals with higher psychiatric comorbidity, lower socioeconomic status, higher unemployment and lower college attendance, as well as other risk factors (e.g., residential instability) that may moderate treatment effectiveness (Worden & McCrady, 2013). Second, although Tevyaw et al (2007) reported significant post-treatment reductions in peer drinking, this study used a short follow up period (i.e., one month).…”
Section: Introduction 10mentioning
confidence: 99%
“…beneficial effect (Martens, Smith, & Murphy, 2013;Worden, & McCrady, 2013). The VAMC system does provide brief advice in primary care for veterans who screen positive on the AUDIT, although this is not typically presented with detailed personalized feedback.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is plausible that this treatment component may be working against the other curative active ingredients when included in MI interventions, and there are anecdotal concerns that this may be more prominent for adolescents. Second, there are important contextual variables that may diminish the effectiveness of NF with adolescents, as brief feedback interventions have rarely been tested in public not-for-profit settings serving racially diverse clients with higher psychiatric comorbidity (Worden & McGrady, 2013). One particular problem with using NF with racial minorities is that they may not believe that norms are specific to their group.…”
Section: Nf: Description Theoretical Foundations and Outcomesmentioning
confidence: 99%
“…Also, this pilot study provides preliminary information on whether the study question warrants additional attention and can inform power analyses for future trials. Finally, we also note the importance of replicating work in this area with a sample of adolescents seen in public not-for-profit settings that are known to serve racially and socioeconomically diverse clients with high psychiatric comorbidity (Dennis, White, & Ives, 2009; Worden & McGrady, 2013). As there is no data to guide hypotheses for adolescent samples, we refrained from making directional hypotheses about how NF would impact RTC, treatment satisfaction, or client-perceived quality of MI.…”
Section: Summary and Hypothesesmentioning
confidence: 99%